2018
DOI: 10.24869/psyd.2018.433
|View full text |Cite
|
Sign up to set email alerts
|

Level of Mother-Baby Bonding and Influencing Factors During Pregnancy and Postpartum Period

Abstract: Background: Bonding is the process of an emotional relationship between mothers and babies. Pregnancy and postpartum periods are most important of developing a mother-child bonding. Here we aimed to determine the level of mother-baby bonding and identify the influencing factors during pregnancy and the postpartum period and to examine the relationship between bonding level during pregnancy and the postpartum period. Subjects and methods: This cross-sectional descriptive study included twelve districts across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
6
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 26 publications
4
58
6
9
Order By: Relevance
“…Many authors underline that low maternal prenatal attachment is associated with low prenatal maternal fetus representations and self-care [25][26][27][28][29] and low postnatal attachment until 24 months postpartum [30][31][32][33][34][35][36][37][38][39]. Additionally, poor parental prenatal attachment has been connected to behavioral and conduct problems, lower cognitive development, and negative socioemotional regulations in early childhood [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors underline that low maternal prenatal attachment is associated with low prenatal maternal fetus representations and self-care [25][26][27][28][29] and low postnatal attachment until 24 months postpartum [30][31][32][33][34][35][36][37][38][39]. Additionally, poor parental prenatal attachment has been connected to behavioral and conduct problems, lower cognitive development, and negative socioemotional regulations in early childhood [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Model 1 was adjusted for age only. In Model 2, we further adjusted the following, which may potentially confound the association between ART and LMIB: maternal age, the babies' sex, incidence of insults from partner during pregnancy, incidence of quarreling within couples during pregnancy, maternal history of depression and anxiety, maternal education and familial economic status, since these factors have been considered to affect mother‐to‐infant bonding in perinatal or post‐partum period, and related to maternal psychological distress among those who received ART . These variables were selected from those listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Catherine's quality-stress model showed that relationship templates dominated by fear or lack of security, such as insecure attachment, may become a personality trait, making women more vulnerable to perinatal depression than those without this trait [10]. The level of prenatal attachment affects maternal-infant attachment after delivery [11]. A study of 165 pregnant women in Poland found that a pregnant woman's type of attachment affects her image as a mother and her connection with her fetus [12].…”
Section: Introductionmentioning
confidence: 99%